2016
DOI: 10.1289/ehp.1510810
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Exposure and Preterm Birth: Estimates of U.S. Attributable Burden and Economic Costs

Abstract: Background:Preterm birth (PTB) rates (11.4% in 2013) in the United States remain high and are a substantial cause of morbidity. Studies of prenatal exposure have associated particulate matter ≤ 2.5 μm in diameter (PM2.5) and other ambient air pollutants with adverse birth outcomes; yet, to our knowledge, burden and costs of PM2.5-attributable PTB have not been estimated in the United States.Objectives:We aimed to estimate burden of PTB in the United States and economic costs attributable to PM2.5 exposure in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 28 publications
1
45
2
1
Order By: Relevance
“…Ozone appears to increase the risk of early delivery, but it decreases the risk of term low birth weight [33]. The estimated annual cost of preterm births associated with air pollution in the United States has been estimated to be about $5 billion with an estimated 3.32 % of the preterm births attributed to PM2.5 being greater than 8.8 micrograms per cubic meter [77]. Sulfur dioxide contributed to low birth weight babies in China [91].…”
Section: Health Effects Of Air Pollutionmentioning
confidence: 99%
“…Ozone appears to increase the risk of early delivery, but it decreases the risk of term low birth weight [33]. The estimated annual cost of preterm births associated with air pollution in the United States has been estimated to be about $5 billion with an estimated 3.32 % of the preterm births attributed to PM2.5 being greater than 8.8 micrograms per cubic meter [77]. Sulfur dioxide contributed to low birth weight babies in China [91].…”
Section: Health Effects Of Air Pollutionmentioning
confidence: 99%
“…It has been shown that in 2010, around 15,808 preterm births within the USA could be attributed to PM2.5 exposure. The concomitant preterm birth cost was estimated at 4 billion USD, of which 760 million USD were spent on medical care (Trasande, Malecha et al, 2016). Another study in South Carolina estimated the incremental costs of comorbidities observed in preterm infants to range from 4.529 to 23.121 USD.…”
Section: The Mutual Influences Of Man-made Pollutants and Allergic Mamentioning
confidence: 99%
“…Trasande et al [3] found the cost of medical care for preterm births attributable to PM 2.5 exposure to be between $2.43 and $9.66 billion. Ghude et al [4] demonstrates the economic cost of poor air quality in India to crop yields is estimated to be around $1.26 billion annually.…”
Section: Introductionmentioning
confidence: 99%